A quick and easy high performance liquid chromatography method for evaluation of cefixime in human plasma - Hossein Danafar (Mazandaran University of Medical Sciences, 2015)
Ceﬁxime is essential member of orally energetic third generation cephalosporin and has tremendous activity aligned with many pathogens. The virtual bioavailability of a newly industrial dispersible tablet as compared with a recognized identified formulation.  A simple and available reversed-phase HPLC method with UV detection has been urbanized and validate for cefixime evaluate in human plasma using a C18 analytical column and a mobile phase of tetrabutylammonium hydroxide (pH 6.5)-acetonitrile (3:1 v/v). The detection wavelength was 280 nm. To method observed major linear response-concentration association all through the cefixime concentration range of 15-100 ng/ml, with the average accuracy within-run and between-run values of 97.29% and 99.27%. The average drug recovery from plasma was 98.2% throughout the linear concentration range. The limits of detection (LOD) and quantitation (LOQ) of the method were 5 and 15 ng/ml, respectively. The method is quick, easy, very steady and precise for the partition, assignment, evaluation of ceﬁxime in human plasma.